The application of injectable platelet-rich fibrin in regenerative dentistry: A systematic scoping review of In vitro and In vivo studies - Nima Farshidfar, DDS; Dana Jafarpour, DDS; Parsa Firoozi, DDS; Sarina Sahmeddini, DDS; Shahram Hamedani, DDS, MSc; Raphael Freitas de Souza, DDS, MSc, PhD; Lobat Tayebi, PhD (Elsevier, 2022)
Background: Ongoing research in the dental field has begun to focus on the use of injectable platelet-rich fibrin (I-PRF) as a regenerative tool with the potential to prompt tissue regeneration. In this regard, this systematic scoping review aimed to collect, map, and appraise the in vitro and in vivo studies regarding the role of I-PRF in or soft and hard tissue regeneration in relation to oral and maxillofacial structures. Methods: A systematic electronic search of Medline, Scopus, Web of Science, and Embase databases was performed from 2000 to December 2021 using a combination of keywords. All in vitro and in vivo studies, written in English and concerning the potential role of I-PRF in regenerative dentistry were considered. Results: In total, 18 in vitro studies, 5 animal studies, 6 case reports, and 31 clinical studies have evaluated the effect of I-PRF on oral and maxillofacial soft and hard tissue regeneration. The investigated studies verified the anti-inflammatory, anti-microbial efficacy and the positive effects of I-PRF application for wound, periodontal, bone, cartilage, and pulp regeneration, as well as acceleration in tooth movement during orthodontic treatment. Conclusions: Current literature approves the feasibility of I-PRF application as a promising regenerative adjunct to dental procedures.